Avaliação da internacionalização na pós-graduação stricto sensu: um estudo na área de administração pública e de empresas, ciências contábeis e turismo - Fernandes, Jardênia de Souza (2019)
In the context of higher education, internationalization is understood as the process of integrating an international, intercultural and global dimension to the purposes, functions and offers of teaching. Its strategies include cooperation projects, institutional and network agreements, academic mobility, curriculum and research (KNIGHT, 2008, 2015). It is a quality indicator and has attracted interest worldwide, in order to verify the internationalization performance. In Brazil, the Ministry of Education (MEC), through the Coordination for the Improvement of Higher Education Personnel (Capes), has been discussing new ways of evaluating Postgraduate Programs (PPGs). In this perspective, the present research aims to evaluate the internationalization in Stricto sensu Graduate Programs with concept 7 and 6 in the area of Public and Business Administration, Accounting Sciences and Tourism (2013- 2016). As for the methodological aspects, it has a descriptive character, application of a mixed method and an intentional non-probabilistic sample. Data collection occurred from documentary sources, with application of content analysis and descriptive statistics of the data. In addition, data collection was guided by the conceptual framework for assessing internationalization suggested by studies by Gao (2015; 2018). The results show that the programs have multiple international partners, with the development of activities “at home” and abroad; absence of offices / international research center; and are offered by national institutions. It also presents a disparity in performance between the dimensions of internationalization. It is concluded, therefore, that these are aspects associated with the Classic Model of internationalization (or 1st generation). This research contributes to the theoretical discussion of the evaluation of internationalization in graduate studies; suggests self-assessment insight to PPGs; and identifies performance aspects in programs of excellence, enabling comparison between peers.